1983
DOI: 10.1177/074391568300200104
|View full text |Cite
|
Sign up to set email alerts
|

Affirmative Disclosure: Long-term Monitoring of Residual Effects

Abstract: In 1973, the Federal Trade Commission charged the manufacturer of Hawaiian Punch fruit drink with deceptive advertising of the proportion of natural fruit juice in the product. A consent order that specified the use of corrective advertising (affirmative disclosure) to correct suspected residual effects was agreed to. The order required that a consumer survey be conducted to demonstrate whether the residual effects had dissipated to an acceptable level. This study presents the results of 11 cross-sectional sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…For HP purchasers and potential purchasers, the proportion of consumers with this belief was less than 20% of the sample. Over the nine-year period, the proportion of consumers who believed that HP contained 20% or less fruit juice gradually rose to approximately 70% (Kinnear, Taylor, and Gur-Arie 1983). Marketing scholars at the time viewed this finding as the glass being 30% empty rather than 70% full, so to speak (Kinnear, Taylor, and Gur-Arie 1983, p. 43; Wilkie, McNeill, and Mazis 1984, p. 24).…”
Section: Historical Efforts To Regulate Use Of “Natural”mentioning
confidence: 99%
“…For HP purchasers and potential purchasers, the proportion of consumers with this belief was less than 20% of the sample. Over the nine-year period, the proportion of consumers who believed that HP contained 20% or less fruit juice gradually rose to approximately 70% (Kinnear, Taylor, and Gur-Arie 1983). Marketing scholars at the time viewed this finding as the glass being 30% empty rather than 70% full, so to speak (Kinnear, Taylor, and Gur-Arie 1983, p. 43; Wilkie, McNeill, and Mazis 1984, p. 24).…”
Section: Historical Efforts To Regulate Use Of “Natural”mentioning
confidence: 99%
“…They found that the product's other attributes, its (true) ad claims, and competitive advertisements all reinforced the false belief. Another study investigating the effects of the corrective advertising ordered in 1973 against Hawaiian Punch fruit drink found that the false beliefs declined steadily over a nine-year period following the fTC order (Kinnear et al 1983). Mazis (2001) has also asserted that an advertisement's memorability (or lack thereof) does not equate to lasting effects on consumers' beliefs.…”
Section: Deceptive Advertising and Consumersmentioning
confidence: 96%
“…for example, in the Hawaiian Punch case, false beliefs declined over time, but 30% of consumers continued to harbour false impressions of the product's fruit juice content, even after eight and a half years of corrective advertising (Kinnear et al 1983). In the case of listerine, misbeliefs also remain, despite the corrective advertising campaign (Armstrong et al 1983).…”
Section: Corrective Remedies By the Ftcmentioning
confidence: 97%
“…In addition, the FTC introduced studies from the marketing literature that revealed that consumer beliefs about established brands tend to change slowly, even when corrective messages are included in advertising. For example, after eight and a half years of corrective advertising for Hawaiian Punch (required by consent order), 30% of consumers continued to hold false impressions about the brand's fruit juice content (Kinnear, Taylor, and Gur-Arie 1983). Also, two studies focusing on changes in consumer beliefs about Listerine found that misbeliefs about Listerine declined between 11% and 20% as a result of a one-and-a-half-year corrective advertising campaign (Armstrong, Gurol, and Russ 1983; Mazis 1981).…”
Section: Lingering Effects Estimationmentioning
confidence: 99%